(untitled) (Multilingual Margins: A journal of multilingualism from the periphery, 2024)
For six years of my life, I lived in Camps Bay. That’s a bit like saying I lived in Beverley Hills, or Knightsbridge, or on The Peak in Hong Kong. Every city has a suburb that is the local byword for conspicuous consumption, for interstellar property values, for self-indulgent wealth. In Cape Town to say you live in Camps Bay is to say your other car is a Range Rover; that your Pilates instructor comes to your house every morning; that your daughter started using Botox at seventeen.